Looking for appropriate forms of intergovernmental transfers for municipalities in transition economies - Chang Woon Nam; Rüdiger Parsche (European Regional Science Association (ERSA), 2002)
Intergovernmental transfers can be either conditional or unconditional with regard to the autonomy of local governments in spending such financial means. Although fiscal decentralisation has recently been quite pronounced in Eastern European transition countries, the dominance of a purpose-and project-oriented, down-flow transfer system is apparent. In adopting abundant matching grants, the central government in these countries will further try to efficiently lead the provision of local public goods and services, which could, however, make the process of carrying-out legally assigned public activities by municipalities less 'self-governing'. On the other hand, the west German municipal resource allocation system ("Kommunalausgleichsystem") was implemented also in the eastern part of the country after unification, which primarily provides unconditional transfers for local governments. Furthermore, in the case of adopting the so-called principle of parallel development of fiscal capacity between the state and municipalities ('Gleichmäßigkeitsgrundsatz'), as Saxony already has done, the intergovernmental transfer ratio is no longer exogenously but endogenously determined, which better guarantees a just resource allocation between the two jurisdictions. Since the subsidiarity principle backed by sufficient own fiscal resources (from local taxes, in particular) and unconditional transfers appears to gradually gain significance in providing local utilities, this study shows the recent Saxon experience with unconditional transfers, which can be a helpful yardstick for the future political discussion aimed at improving the fiscal develolution system in many Easten European transition economies.
Keywords: 330